2016
DOI: 10.1002/prca.201600086
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein profiling studies of β‐thalassemia/Hb E disease

Abstract: A number of studies have used global protein profiling technologies on a range of patient samples to detect proteins that are differentially expressed in β-thalassemia/Hb E as an aid for understanding the physiopathology of this disease. Seven studies have identified a total of 111 unique, differentially expressed proteins. Seven proteins (prothrombin, alpha-1-antichymotrypsin, fibrinogen beta chain, hemoglobin beta, selenium-binding protein, microtubule-actin cross-linking factor and adenomatous polyposis col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…This study, and the study by Karmakar 19 , only identified one protein in common, namely Hsp70. However, as reviewed elsewhere multiple studies determining the differences in proteomes between β-thalassemia/HbE patients and healthy volunteers rarely identify common proteins as a consequence of the usage of different samples sources (erythrocytes, platelet free plasma derived microparticles, plasma, etc) and different analysis methodologies, as extensively reviewed elsewhere 20 . In this regard we found higher serum ferritin levels in splenectomized patients than in non-splenectomized patients and healthy volunteers in contrast to the previous study 19 .…”
Section: Discussionmentioning
confidence: 99%
“…This study, and the study by Karmakar 19 , only identified one protein in common, namely Hsp70. However, as reviewed elsewhere multiple studies determining the differences in proteomes between β-thalassemia/HbE patients and healthy volunteers rarely identify common proteins as a consequence of the usage of different samples sources (erythrocytes, platelet free plasma derived microparticles, plasma, etc) and different analysis methodologies, as extensively reviewed elsewhere 20 . In this regard we found higher serum ferritin levels in splenectomized patients than in non-splenectomized patients and healthy volunteers in contrast to the previous study 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional gel electrophoresis (2-DE) coupled with mass spectrometry or tandem mass spectrometry (MS and MS/MS) has been used for the investigation of β-thalassemic proteomes. The majority of differential expressed proteins between β-thalassemia patients and normal clinical specimens have been identified and characterized their functions in different metabolic processes in response to inorganic substances using an online DAVID gene ontological analysis [54]. Several enzymes in metabolic processes are usually abundant and easily found on the 2-DE, whereas low-abundant proteins involve in gene regulation and signal transduction cascades are difficult to detect.…”
Section: Gel-based Techniquementioning
confidence: 99%
“…In addition, PXD2 has function in stress response in the protective system during stress erythropoiesis in thalassemic mice model [61]. PXD2 is an abundant protein mostly identified in many proteomic studies from various clinical specimens of β-thalassemia [50,54,62]. An increased oxidative damage from alpha excess and iron overload thus triggers the cellular defensive mechanism, including antioxidative responses.…”
Section: Oxidative Damage and Antioxidant Proteinsmentioning
confidence: 99%
“…These gene alterations often cause either a decrease in β-globin synthesis or completely block synthesis [ 13 ]. For example, HbE/β-thalassemia is a G A substitution at the 26 position of the β-globin gene and replaces Glu with Lys, resulting in a decrease in the β-globin chain [ 14 , 15 , 16 , 17 ]. As such, 1–3% of the people in Southern China carry a β-thalassemia allele and over 20 β-thalassemia mutations have been reported in the Chinese population [ 18 ].…”
Section: Introductionmentioning
confidence: 99%